2021
DOI: 10.4103/jpbs.jpbs_222_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Ormeloxifene on Multiple Fibroadenomas and Mastalgia

Abstract: Introduction: Most common benign breast conditions presenting in the breast clinics include fibroadenomas and mastalgia, both these conditions cause considerable anxiety in the patients. Among other treatment modalities, the hormonal drug treatments are gaining popularity. Ormeloxifene (centchroman) is an antiestrogenic drug which is shown to have effect in reducing the pain in mastalgia patients and the size of fibroadenoma. Objectives: Ormeloxifene is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another observational study by Brahmachari et al 17 . reported that only 3% patients had complete regression of fibroadenoma at the end of 3 months with 30 mg Ormeloxifene on alternate days and it increased to 30% at the end of 6 months.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Another observational study by Brahmachari et al 17 . reported that only 3% patients had complete regression of fibroadenoma at the end of 3 months with 30 mg Ormeloxifene on alternate days and it increased to 30% at the end of 6 months.…”
Section: Discussionmentioning
confidence: 96%
“…[14][15][16] However, previous studies of Centchroman for the medical management of fibroadenoma have shown contradictory effects. 10,17 We evaluated the efficacy of Ormeloxifene (Centchroman) on regression of Fibroadenoma in this double-blind placebo-controlled trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormones, such as estrogen and progesterone, influence the size and behavior of fibroadenomas, leading to variations in pain perception. This clinical feature highlights fibroadenomas' dynamic nature and responsiveness to hormonal changes, underscoring the importance of considering hormonal influences in their clinical evaluation [ 32 ].…”
Section: Reviewmentioning
confidence: 99%